Evaluation of Inbred Line Through Line X Tester Method (Journal of Environmental Science and Natural Resources, 2015)
Early generation evaluation of inbred lines through line × tester method was conducted at Regional Agricultural Research Station, Rahmatpur during rabi 2013-14 in maize involving 12 S4 lines and 2 testers (BIL 28 and BIL 29) for grain yield, yield components and other characters to estimate the general combining ability of the lines and specific combining ability effects of the crosses. Highly significant genotypic differences were observed indicated wide range of variability present among them. The crosses with high SCA effect for grain yield evolved from high × low general combiner parents were revealed additive x dominance type of gene action. The cross combinations E-7 X BIL-29, E-11 X BIL-29, E-10 X BIL-28 and E-9 X BIL-28 with high positive SCA effect having high mean values might be used for obtaining high yielding hybrids. The information on the nature of gene action with respective variety and characters might be used depending on the breeding objectives.DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22211 J. Environ. Sci. & Natural Resources, 7(2): 79-84 2014